(untitled) (REMUNOM, 2025)
This article discusses public policies for environmental preservation in the municipality of Porto Velho, in the state of Rondônia. The aim is to understand which governmental actions have been established and how they have contributed to the maintenance and conservation of natural resources amidst constant social, economic, and cultural changes. The research is based on a qualitative approach with a bibliographic and documentary character, using environmental legislations—such as Law No. 1,224—master plans, data from the Brazilian Institute of Geography and Statistics (IBGE), and reports from the Municipal Department of the Environment. These analyses show that, although there are normative proposals and specific actions aimed at environmental preservation in Porto Velho, such as reforestation projects, awareness campaigns, and the creation of protected areas, structural limitations are still observed in areas such as inspection, solid waste management, and the implementation of policies. Public policies often lack coordination among different levels of government and dialogue with the local population, which compromises their effectiveness. The study also highlights the importance of including traditional knowledge and local practices in environmental planning, valuing the cultural and ecological diversity of the Amazon region. In this sense, it is evident that the challenges for environmental preservation in Porto Velho require integrated actions, continuous planning, institutional strengthening, and active social participation in order to ensure the sustainable use of natural resources and environmental balance.